SAUDI ALLIED HEALTH PROFESSIONALS’ INSIGHTS ON PATIENT SAFETY: PERSPECTIVES OF DENTAL ASSISTANTS, NURSE TECHNICIAN, LABORATORY TECHNICIANS, RADIOLOGY TECHNICIANS, AND MEDICAL SECRETARIES - Wafa Saad Aljulaidan, Nahed Jazza Alshammari, Fatimah Abdrabalrasool Sukair, Reem Mohamed Bohameil, Hifa Fahad Aljalaidan, Nouf Mohammed Bohameil, Heba Saad Aljulidan (Chelonian Research Foundation, 2022)
Patient safety is a critical component of healthcare delivery, and allied healthprofessionalsplayavitalroleinensuringthewell-beingofpatients.Thisqualitativestudyexplorestheperspectivesofdentalassistants,nurse technician,laboratory technicians, radiology technicians, and medical secretaries on patient safetyin Saudi Arabia. Semi-structured interviews were conducted with 20 participants, andthematic analysis was employed to identify key themes. The findings reveal that alliedhealthprofessionalsfacevariouschallengesinmaintainingpatientsafety,includingcommunicationbarriers,inadequatetraining,and resource constraints.Participantsalso highlighted the importance of teamwork, patient-centered care, and continuousquality improvement in promoting a culture of safety. The study provides valuableinsights into the experiences and perceptions of allied health professionals and offersrecommendationsforenhancingpatientsafetyinSaudihealthcaresettings. Keywords: patient safety, allied health professionals, qualitative research, SaudiArabia